New evidence for coupled clock regulation of the normal automaticity of sinoatrial nodal pacemaker cells: bradycardic effects of ivabradine are linked to suppression of intracellular Ca(2+) cycling: Dual effects of ivabradine on Ca(2+) and membrane clocks - Yaniv, Yael (2013)
Beneficial clinical bradycardic effects of ivabradine (IVA) have been interpreted solely on the basis of I(f) inhibition, because IVA specifically inhibits I(f) in sinoatrial nodal pacemaker cells (SANC). However, it has been recently hypothesized that SANC normal automaticity is regulated by crosstalk between an “M clock,” the ensemble of surface membrane ion channels, and a “Ca(2+) clock,” the sarcoplasmic reticulum (SR). We tested the hypothesis that crosstalk between the two clocks regulates SANC automaticity, and that indirect suppression of the Ca(2+) clock further contributes to IVA-induced bradycardia. IVA (3μM) not only reduced I(f) amplitude by 45±6% in isolated rabbit SANC, but the IVA-induced slowing of the action potential (AP) firing rate was accompanied by reduced SR Ca(2+) load, slowed intracellular Ca(2+) cycling kinetics, and prolonged the period of spontaneous local Ca(2+) releases (LCRs) occurring during diastolic depolarization. Direct and specific inhibition of SERCA2 by cyclopiazonic acid (CPA) had effects similar to IVA on LCR period and AP cycle length. Specifically, the LCR period and AP cycle length shift toward longer times almost equally by either direct perturbations of the M clock (IVA) or the Ca(2+) clock (CPA), indicating that the LCR period reports the crosstalk between the clocks. Our numerical model simulations predict that entrainment between the two clocks that involves a reduction in I(NCX) during diastolic depolarization is required to explain the experimentally AP firing rate reduction by IVA. In summary, our study provides new evidence that a coupled-clock system regulates normal cardiac pacemaker cell automaticity. Thus, IVA-induced bradycardia includes a suppression of both clocks within this system.